Simultaneous Surface Display and Holography Enabled by Flat Liquid Crystal Elements. Issue 7 (8th April 2022) - Tang, Dongliang; Shao, Zhenglong; Zhou, Yingjie; Lei, Yu; Chen, Long; Xie, Jin; Zhang, Xiaohu; Xie, Xin; Fan, Fan; Liao, Lei; Wen, Shuangchun
Abstract: As a fundamental material in the current mainstream display technology, liquid crystal (LC) exhibits excellent properties including controllable and reconfigurable LC orientation, high‐efficiency pure‐phase modulation, active tunability, etc., and becomes one of the most attractive candidates for the development of next‐generation flat optical devices. Current LC elements are suffering from the single functionality as only one type of the optical manipulation is involved. Integrating several functions together brings great flexibility and high integration but remains an urgent task. Here, flat LC elements are proposed to simultaneously accomplish near‐field display and far‐field holography. The anisotropic nature of the LC allows a complex amplitude modulation with a sinusoidal variation, promising a continuous amplitude change, and a binary phase modulation. Specifically, several two‐channel LC elements are experimentally demonstrated, which simultaneously generate a grayscale pattern at sample surface and project an independent holographic image in the far field. Furthermore, the position and spatial multiplexing methodologies are introduced to further improve the information capacity. The proposed LC elements with simple anisotropic structure and large fabrication size can empower the multifunctional design and have promising prospects in information multiplexing, image displaying, data storage, etc. Abstract : Current liquid crystal (LC) elements are suffering from the single functionality as only one type of the optical manipulation is involved. A flat element, merely composed of anisotropic LC molecules with varying orientations, is designed to generate a grayscale pattern at sample surface, at the same time, project an independent holographic image in the far field.